Hubungan Asosiasi Antara Daerah Asal Mahasiswa Dalam Keaktifan Berorganisasi Di Universitas Sultan Ageng Tirtayasa - Muhammad Ibnu Dzikraa F; Imelda Khairunnisa; Fadila Salva Swastika; Agung Firmansyah; Roffif Robbani (Pusat Riset dan Inovasi Nasional, 2023)
In simple terms, an organization can be defined as a unit that serves as a container or means to achieve various goals or objectives. It has many components that underlie it, including many people, work relationships, job specialization, and rational awareness of members according to their respective abilities and specializations. However, student activity in organizations is influenced by the origin of the students because each region has different cultural values. The origin of students determines the choice of organizations and organizational activity followed. This study aims to determine whether there is a relationship between the origin of students and organizational activity on the campus of Sultan Ageng Tirtayasa University. This research uses a questionnaire research method using Google Forms. The population subjects in this study were all students of Sultan Ageng Tirtayasa University by taking a sample of 56 students. Data collection techniques used multiple-choice questions consisting of only 2 valid and reliable questions.